The Rule of Law and the Rule of God
VII, 284 p.
Keywords: This book examines the competing regimes of law and religion an offers a multidisciplinary approach to demonstrate the global scope of their influence. It argues that the tension between these two institutions results from their disagreements about the kinds of rule that should govern human life and society, and from where they should be derived.